From HR model to contextual system: An exploration of how the HR function is organised and the factors that influence the organising of HR - Cooper, Jessica (Cranfield University, 2024)
This research examines the organisation of the Human Resources (HR) function. The narrative from the profession has been dominated by a single model, the ‘Ulrich model’ (Ulrich et al., 2008) that has influenced the way that HR functions organise; however, there is limited empirical research which has examined the organisation of HR in practice. Research in this area of HR has focused upon examining individual elements such as shared services, outsourcing etc. and there has been a lack of holistic examination. For this reason, little is understood about what influences the organisation of HR and there is an absence of theoretical explanation. At a time when the HR function has increased its standing in the organisation following COVID-19 and the aftermath, and as organisations go through a period of rapid change requiring the support of HR, it is important that HR is capable of continuing to be an integral part and meet the needs of the organisation.
Keywords: Human Resources organisation; HR organisation in practice; shared services; outsourcing; holistic examination; meeting needs